Reading Monuments A Comparative Study of Monuments in Poznań and Strasbourg from the Nineteenth and Twentieth Centuries - Praczyk, Małgorzata (Studies in Contemporary History, 2020)
This book tells the story of monuments in two cities that share a parallel and turbulent history: Strasbourg and Poznan. With the Franco-Prussian War begins the well-known story of the destruction and erection of memorials. This book not only explains the mechanisms related to how memorials have functioned in the past, but also contributes to our understanding of current modes of their perception. It analyzes their material shape, the problem of affect, and their meaning, not only in relation to the political context and the work of memory. This book shows how the form of monuments reflects the social understanding of such basic questions as the perception of nature, gender issues and the image of those who are in power, and how, and in which aspects, those kind of objects actually change the city space we live in.